Do low-income households in Tanzania derive income and nutrition benefits from dairy innovation and dairy production? - Kidoido, Michael M.; Korir, Luke (Springer, 2015)
Although the role of Animal Source Foods (ASFs) in household nutrition is well established, dairy development as a mechanism for reducing poverty and malnutrition is inadequately understood. This study investigated the differences across income strata in contributions of dairy innovations and dairy production to dairy income and nutrition outcomes. Analysis was based on the Tanzania Living Standards Measurement Study-Integrated Surveys on Agriculture (LSMS-ISA) household panel data of 2008/2009 and 2010/2011. The role of dairy innovations in household income and the importance of dairy income in expenditure on food were estimated using Two-Stage Least-Squares (2SLS). Seemingly Unrelated Regression (SUR) to analyze the effect of dairy consumption on nutrition outcomes of children below 5 years of age. Although dairy innovations had a positive effect on dairy income, the effect was small among low income households due to their lack of comparative advantage in accessing and using inputs, output markets and services. Also, their reliance on low productivity dairy animals affected their potential dairy income. Consumption of dairy products in low-income households was associated with reduced stunting, underweight and wasting. Wasting in high-income households was only significant among girls. Whereas adoption of dairy innovations and consumption of dairy products have great potential for improving the income and nutrition of low-income households, pro-poor dairy interventions should also be integrated with increasing access to markets and services. Interventions should also incorporate strong gender aware approaches to ensure that the benefits are shared equitably within households.